Vascular hyperpermeability as a hallmark of phacomatoses: is the etiology angiogenesis related to or comparable with mechanisms seen in inflammatory pathways? Part II: angiogenesis- and inflammation-related molecular pathways, tumor-associated macrophages, and possible therapeutic implications: a comprehensive review - Laviv, Yosef; Kasper, Burkhard; Kasper, Ekkehard M. (Neurosurgical Review, 2018)
Phacomatoses are a special group of familial hamartomatous syndromes with unique neurocutaneous manifestations as well as characteristic tumors. Neurofibromatosis type 2 (NF2) and tuberous sclerosis complex (TSC) are representatives of this family. A vestibular schwannoma (VS) and subependymal giant cell tumor (SGCT) are two of the most common intracranial tumors associated with these syndromes, related to NF2 and TSC, respectively. These tumors can present with an obstructive hydrocephalus due to their location adjacent to or in the ventricles. Remarkably, both tumors are also known to have a unique association with elevated protein concentrations in the cerebrospinal fluid (CSF), sometimes in association with a non-obstructive (communicating) hydrocephalus. Of the two, SGCT has been shown to be associated with a predisposition to CSF clotting, causing a debilitating recurrent shunt obstruction. However, the exact relationship between high protein levels and clotting of CSF remains unclear, nor do we understand the precise mechanism of CSF clotting observed in SGCT. Elevated protein levels in the CSF are thought to be caused by increased vascular permeability and dysregulation of the blood-brain barrier. The two presumed underlying pathophysiological processes for that in the context of tumorigenesis are angiogenesis and inflammation. Both these processes are correlated to the phosphatidylinositol-3-kinase/Akt/mammalian target of rapamycin pathway which is tumorigenesis related in many neoplasms and nearly all phacomatoses. In this review, we discuss the influence of angiogenesis and inflammation pathways on vascular permeability in VSs and SGCTs at the phenotypic level as well as their possible genetic and molecular determinants. Part I described the historical perspectives and clinical aspects of the relationship between vascular permeability, abnormal CSF protein levels, clotting of the CSF, and communicating hydrocephalus. Part II hereafter describes the different cellular and molecular pathways involved in angiogenesis and inflammation observed in both tumors and explores the existing metabolic overlap between inflammation and coagulation. Interestingly, while increased angiogenesis can be observed in both tumors, inflammatory processes seem significantly more prominent in SGCT. Both SGCT and VS are characterized by different subgroups of tumor-associated macrophages (TAMs): the pro-inflammatory M1 type is predominating in SGCTs, while the pro-angiogenetic M2 type is predominating in VSs. We suggest that a lack of NF2 protein in VS and a lack of TSC1/TSC2 proteins in SGCT significantly influence this fundamental difference between the two tumor types by changing the dominant TAM type. Since inflammatory reactions and coagulation processes are tightly connected, the pro-inflammatory state of SGCT may also explain the associated tendency for CSF clotting. The underlying cellular and molecular differences observed can potentially serve as an access point for direct therapeutic interventions for tumors that are specific to certain phacomatoses or others that also carry such genetic changes.
EVALuna2:36313